Ecological preferences and patient autonomy - Salloch, Sabine (Journal of medical ethics, 2025)
Healthcare systems contribute considerably to worldwide carbon emissions and therefore reinforce the negative health impacts of climate change. Significant attempts to reduce emissions have been made on the macro level of politics and on the institutional level. Less attention has been paid so far to decisions that take place at the micro level of immediate doctor-patient contact. Current bioethical debates discuss potential tensions between ‘Green Healthcare’ and an orientation towards ethical principles such as promoting patient welfare or respect for patient autonomy. The article addresses this debate from a different angle starting from the premise that at least some patients might have a preference to reduce carbon outputs that are often deeply rooted in their personal value system. Taking different accounts of patient autonomy as a starting point, the article analyses whether such preferences must be respected as being part of patient autonomy. The analysis comes to a positive conclusion but highlights that certain factors such as misinterpretation, lack of understanding or pressure must be carefully considered. In addition, a patient's climate-related preference does not per se justify the choice of treatment but must be integrated into shared decision-making and reconciled with the healthcare professional's expert judgement on the intervention being a legitimate and promising way for reaching certain treatment goals. As a recommendation, empirical research on stakeholders' attitudes, knowledge and practice regarding ecological sustainability in clinical decision-making is needed together with further ethical analyses.